Response of soybean genotypes to salinity in germination stage - PRATANTI HAKSIWI PUTRI; GATUT WAHYU ANGGORO SUSANTO; RINA ARTARI (Smujo International, 2017)
Putri PH, Susanto GWA, Artari R. 2017. Response of soybean genotypes to salinity in germination stage. Nusantara Bioscience 9: 133-137. Salinity is one of the agricultural problem, especially in marginal land. The negative impact of salinity for plants such as delay germination time, growth inhibition, reduce nodules formation, decrease biomass accumulation, and reduce yield quantity and quality. Initial selection for salt resistance of soybean, conducted on 16 genotypes, using three levels of NaCl and three replications. Germination conducted for six days, in germinator which has been set at 25oC, with lighting. Mean Germination Time (MGT), Final Germination Percent (FGP), sprout length (root and overall) and weight (fresh and dry), seedling vigor index (length and weight) were observed. Data were analyzed using ANOVA, followed by LSD at 5%. Sixteen soybean genotypes show inhibition effect of salinity. The results showed that 125 mM NaCl does not inhibit germination but it causes abnormal growth at some genotypes. Number of normal germination decreased 20-30% at 125 mM NaCl. Sprouts total length declined by 17-58% at 75 mM and 45-78% at 125 mM NaCl. Root length decrease from 23.2-55.3% at 75 mM and 52.1-81.2% in 125 mM. Fresh weight diminish by 3.8-39.9% at 75 mM and 12.7-52.5% at 125 mM NaCl. Response of sixteen soybean genotypes into salinity stress is clearly visible at sprout length and fresh weight variable. Ichiyou was salt-sensitive based on all variable especially sprout length and fresh weight, while Baluran was salttolerant up to 125 mM NaCl based on sprout length and fresh weight.